Adolescents and School Asthma Knowledge and Attitudes - Leiria-Pinto, P (1999)
Introduction: bronchial asthma is a chronic disease that affects a high percentage of adolescents, with a significant restriction of daily activities, and is a cause of school absenteeism. The relationships between adolescents and asthma disease in school were assessed, with a view to improving knowledge about the asthmatic adolescent. Methods: a survey was conducted in the Lisbon metropolitan area, covering urban (Lisbon) and rural (Lourinh˜a ) zones and including 1879 students and 81 teachers from the 7th to 9th high school years. The study groups were asthmatic students, their peers, and teachers. A self-administered questionnaire was applied to collect information. The results were compared with a reference group of 91 asthmatic students attending our Department of Immunoallergy-Hospital Dona Estefânia. Cotinine urinary measurements were made in a sample of asthmatics and a control group. Results: the prevalence of current asthma among students was 10%. Estimates of asthma annual burden among 7th to 9th year students from Lisbon and Lourinh˜a high schools included 4,307 days missed from school, 4,148 medical consultations and a minimum of 351 hospital emergency care and 80 hospital admissions. Exposure to passive smoking was not significantly different between asthmatic students and theirs peers. Cotinine urinary measurements did not discriminate between exposed and non-exposed individuals. Cigarette smoking was almost as common among adolescent asthmatics (5.4%) as it was in non-asthmatic subjects (6.7%). However, 55% of asthmatics mentioned active and passive smoking as an asthma exacerbating factor. Asthmatic students, theirs peers and teachers showed a deficient knowledge about asthma (mean group scores: 17.6; 14.2 and 17.7 of a possible 30), particularly in the areas related to asthma recognition and its management. Asthmatics attending our Allergy Department had the highest scores. All groups showed tolerance in the sense of a positive and understanding attitude toward a person with asthma. However, traditional beliefs about asthma disease (dependence, inferiority...) were confirmed. A positive correlation between knowledge levels and tolerance attitudes was found. Conclusion: in view of the dimension of the asthma problem in adolescence and its social and economic impact, it is justifiable to assess the need for the implementation of asthma education programs in schools in order to improve asthma management by the adolescents and their schools.